Different Non-cage Housing Systems Alter Duodenal and Cecal Microbiota Composition in Shendan Chickens - Wan, Yi; Ma, Ruiyu; Zhang, Hongyi; Li, Ling; Chai, Lilong; Qi, Renrong; Liu, Wei; Li, Junying; Li, Yan; Zhan, Kai (Frontiers in Veterinary Science, 2021)
Housing systems are among the most important nongenetic factors affecting hen production performance and intestinal microbes. With increased interest in animal welfare, cage-free laying hen housing systems have become common, providing behavioral freedom and health benefits. The present study aimed to compare the effects of plastic net housing system (NRS) and floor litter housing system (LRS) on the composition and function of the duodenal and cecal microbiota in Shendan chicken, one of the most popular laying hen strains in China. The associations between the differential microbiota abundance and production traits and intestinal morphological parameters were determined. Compared with the LRS, the NRS improved the laying rate (p <0.05) and increased the villus height (VH) of the duodenum (p <0.05) and the VH-to-crypt depth ratio (VCR) of the cecum (p <0.05). Alpha diversity analysis showed that LRS chickens had a significantly higher diversity and richness than NRS chickens. Beta diversity analysis demonstrated differences in the microbiota composition based on housing systems. Within the cecum, Proteobacteria and Kiritimatiellaeota were significantly more abundant in the LRS than in the NRS (p <0.05), while Bacteroidetes were significantly less abundant in the LRS (p <0.05). Phascolarctobacterium and Ruminococcaceae_UCG-005 were significantly less abundant in the LRS (p <0.05) compare to the NRS. Within the duodenum, Lactobacillus was significantly less abundant in the LRS (p <0.05) than in the NRS, while Pseudomonas was significantly more abundant in the LRS (p <0.05). Cecal Phascolarctobacterium and Ruminococcaceae_UCG-005 were significantly positively correlated with eggshell strength (R= 0.608, p <0.01) and egg weight (R=0.526, p <0.05), respectively. Duodenal Lactobacillus was significantly positively correlated with VH and VCR (R=0.548 and 0.565, p <0.05),while Pseudomonas was significantly negatively correlated with the Haugh unit (R= -0.550, p <0.05). In conclusion, there are differences in the cecal and duodenal microbiota compositions of Shendan laying hens reared in different non-cage housing systems, and the NRS was superior to the LRS in improving the laying performance and intestinal morphology and microecological environment.